2016
DOI: 10.1097/meg.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Fecal calprotectin for the prediction of small-bowel Crohn’s disease by capsule endoscopy: a systematic review and meta-analysis

Abstract: Fecal calprotectin has a significant diagnostic accuracy for the detection of small-bowel CD. Our results suggest that in patients with suspected CD with calprotectin <50 μg/g, the likelihood of positive diagnosis is very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 34 publications
5
79
0
3
Order By: Relevance
“…21, 22 Although isolated small bowel CD represents a small percentage (2.9%–13%) 23, 24 of newly diagnosed pediatric CD, unrecognized or poorly treated small bowel Crohn’s can lead to significant complications. Additional research is needed to determine the accuracy of CD64 testing in patients with isolated small bowel Crohn’s as we had a limited number (9/60) of L1 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…21, 22 Although isolated small bowel CD represents a small percentage (2.9%–13%) 23, 24 of newly diagnosed pediatric CD, unrecognized or poorly treated small bowel Crohn’s can lead to significant complications. Additional research is needed to determine the accuracy of CD64 testing in patients with isolated small bowel Crohn’s as we had a limited number (9/60) of L1 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…An FC of 50 μg/g had a sensitivity of 83%, a specificity of 53%, and a DOR of −5.64. The study suggested that in patients with less than 50 μg/g, the likelihood of positive diagnosis is very low …”
Section: Resultsmentioning
confidence: 98%
“…This limit has been overcome by lowering FC cutoff, in most of the studies using CE. In this regard, a meta‐analysis by Kopylov showed that an FC concentration > 50 μg/g had 83% sensitivity, but only 53% specificity for active CD . On the other hand, the excellent NPV suggests that the likelihood of CD‐related lesions is poor when FC is < 50 μg/g and ileocolonoscopy is negative.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta-analysis has shown that elevated FC in patients with normal ileocolonoscopy was associated with active small bowel inflammation [45].…”
Section: Faecal Calprotectinmentioning
confidence: 99%